Statistical Estimation of ideal and realistic muon interaction on Al, Fe, and Cu absorbers. Issue 1 (April 2020) - Norizan, M I H M; Hashim, I H; Ibrahim, F; Ghani, N N A M A
Abstract: Interaction of charged muons in various absorbing materials is almost similar to other charged particles. Their behaviour has been observed by various experimental work in material science and nuclear and particle physics. A statistical model is developed in order to study the behaviour of muons after interacting with absorbing material. In this study, ideal and realistic beam structure from high intensity muon facility around the world such as at Japan Accelerator Research Complex, Research Centre Nuclear Physics, Osaka University and Paul Scherrer Institute is assumed. Three absorbing materials (aluminium, iron and copper) with thickness range of 0.00 ˜ 0.12 g/cm 2 are used to observe the momentum straggling of the beams. Performance for our model was checked by comparing the value of stopping power with others work for muons with initial kinetic energy of 10-40 MeV with and without including shell effect correction term. The effect of the energy losses towards the beam structure will be discussed.